Comparing the lexical similarity of the triarchic model of psychopathy to contemporary models of psychopathy. Issue 4 (11th September 2017) - Gatner, Dylan T.; Douglas, Kevin S.; Hart, Stephen D.
Abstract: Objective: The triarchic model of psychopathy (Patrick, Fowles, & Krueger, 2009 ) posits that psychopathic personality comprises three domains: boldness, meanness, and disinhibition. The present study aimed to clarify conceptual overlap between contemporary definitions of psychopathy, with particular emphasis given to the relevance of boldness (i.e., social dominance, venturesomeness, emotional resiliency)—a topic of recent debate. Method: Undergraduate students ( N  = 439) compared the lexical similarity of triarchic domains with two contemporary models of psychopathy: the Comprehensive Assessment of Psychopathic Personality (CAPP; Cooke, Hart, Logan, & Michie, 2012 ) and the Five‐Factor Model of psychopathy (FFM; Widiger & Lynam, 1998 ). Results: From a content validity perspective, meanness and disinhibition were lexically similar to both the CAPP and FFM psychopathy, whereas boldness was less strongly associated with these models. Meanness showed the strongest lexical similarity in comparison with past prototypicality ratings of the CAPP and FFM psychopathy. Conclusions: These findings bear implications for defining and comparing conceptualizations of psychopathy that underpin its assessment.